Research progress and application prospect of nature-based solutions in China - He, Xiangyu; Wei, Hongbin; Li, Shaoshuai (Frontiers in Environmental Science, 2023)
In recent years, Nature-based Solutions (NbS) have become an important concept in the field of climate change and sustainable development. The study screens academic journals relevant NbS researches using China National Knowledge Infrastructure (CNKI) and Web of Science database to explore different perspectives for NbS research through qualitative analysis. This study reviews the existing research on NbS, summarizes what research ideas are covered by NbS, as well as the relationship between previous relevant studies, focuses on different perspectives of refining the implementation of NbS in various studies and practices, and explains them with typical cases. The research shows that existing NbS researches mostly prefer to determine schemes by objects, with insufficient emphasis on subjects and goals. On this basis, the specific operational framework of promoting NbS in China is considered to promote the development of indigenous application of NbS in China. This study reveals the diversified ideas in the research and implementation of NbS at home and abroad, which is of practical significance to promote the localization of NbS in China.